МЕЖНАЦИОНАЛЬНЫЙ БРАК КАК ОДИН ИЗ ПУТЕЙ НАТУРАЛИЗАЦИИ КОРЕЙЦЕВ В ЯПОНИИ (Journal of Oriental Studies, 2016)
In given article features of occurrence of in-ternational marriages of the Korean minority in Japan in the XX-th century are considered. The conclusion of international marriages is studied as one of ways of naturalization of Koreans In Japan. Studying dynamics of mixed marriages, the author puts a problem japanesation Koreans in Japan.